Emerging functions of C/EBPβ in breast cancer - Matherne, Megan G.; Phillips, Emily S.; Embrey, Samuel J.; Burke, Caitlin M.; Machado, Heather L. (Frontiers in Oncology, 2023)
Breast tumorigenesis relies on complex interactions between tumor cells and their surrounding microenvironment, orchestrated by tightly regulated transcriptional networks. C/EBP is a key transcription factor that regulates the proliferation and differentiation of multiple cell types and modulates a variety of biological processes such as tissue homeostasis and the immune response. In addition, C/EBP has well-established roles in mammary gland development, is overexpressed in breast cancer, and has tumor-promoting functions. In this review, we discuss context-specific roles of C/EBP during breast tumorigenesis, isoform-specific gene regulation, and regulation of the tumor immune response. We present challenges in C/EBP biology and discuss the importance of C/EBP isoform-specific gene regulation in devising new therapeutic strategies.